Number of nephrologists, hemodialysis services, and prevalence trend of chronic kidney disease in the ministry of health of Peru - Herrera Añazco, Percy (2019)
We conducted a descriptive and ecological study that evaluated the relationship between the prevalence trend of patients with chronic kidney disease (CKD), the number of nephrologists, and the number of hemodialysis services of the Ministry of Health (MINSA). The study was based on a secondary analysis of the care provided by MINSA, the Observatory of Human Resources in Health, and the hemodialysis services registered as Health Service Providers of the Intangible Health Solidarity Fund (FISSAL, in Spanish). The adjusted prevalence of CKD was found to have increased from 0.5 to 1.5 per 1,000 patients between 2010 and 2017. The regions with the greatest increase were Tumbes, Ucayali, and Piura. The number of nephrologists per 1,000 CKD patients decreased from 4.4 in 2010 to 1.9 in 2016; and the hemodialysis services contracted by FISSAL increased from 16 in 2012 to 74 in 2019.